2014
DOI: 10.1074/jbc.m114.570051
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Signaling via Transcription Factors NF-κB and AP1/c-Fos Mediates Endothelial Cell STIM1 Expression and Hyperpermeability in Response to Endotoxin

Abstract: Background: STIM1 activates store-operated Ca 2ϩ entry (SOCE). The transcriptional regulation of STIM1 during sepsis is not known. Results: STIM1 expression occurs downstream of TLR4 via activation of NF-B and p38␣-mediated c-Fos expression in endothelial cells. Conclusion: Cooperative signaling of NF-B and p38 MAPK downstream of TLR4 is essential for STIM1 expression during sepsis. Significance: Selective p38␣ inhibitors may represent a potential therapeutic strategy to prevent sepsis-mediated lung vascular l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 53 publications
(89 reference statements)
6
40
0
Order By: Relevance
“…Little is known about the regulation of the abundance of STIM1, which could also affect channel function. In this regard, the transcription factor NF-B has been recently reported to promote STIM1 protein expression in mast cells and in vascular endothelial cells (7,12). In the present study, we showed that HNF4␣, a nuclear transcription factor, regulated STIM1 expression by functioning as a repressor in MCs.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Little is known about the regulation of the abundance of STIM1, which could also affect channel function. In this regard, the transcription factor NF-B has been recently reported to promote STIM1 protein expression in mast cells and in vascular endothelial cells (7,12). In the present study, we showed that HNF4␣, a nuclear transcription factor, regulated STIM1 expression by functioning as a repressor in MCs.…”
Section: Discussionsupporting
confidence: 58%
“…Because HNF4␣ expression is tissue specific (11,23,41), our results suggest that transcription factor-regulated STIM1 expression might be cell context dependent. Indeed, we failed to observe an NF-B effect on STIM1 expression in MCs (data not shown), as previously described in mast cell and pulmonary vascular endothelial cells (7,12). HNF4␣ is generally thought as a transcriptional activator and is known to activate a wide variety of genes involved in glucose, fatty acid, cholesterol, and amino acid metabolism (18,20,31,45).…”
Section: Discussionsupporting
confidence: 56%
“…The Ca 2þ concentration was measured using the Ca 2þ -sensitive fluorescent dye Fura-2/AM, as described previously (58). Briefly, cells were grown to confluence on fibronectin-coated coverslips, then washed with Hanks balanced salt solution (HBSS), loaded with 3 mM Fura-2 for 30 min in HBSS, then washed again three to four times with Ca-free HBSS and mounted on a slide holder to a semimotorized microscope (Axio Observer D1, Carl Zeiss, Jena, Germany) equipped with an AxioCam HSm camera (Carl Zeiss) and a Fluar 40Â oil immersion objective.…”
Section: Measurements Of Cytosolic Ca 2þmentioning
confidence: 99%
“…However, we hypothesize that a direct activation of neuronal TLR4 would require local tissue infection or endotoxin extravasation. The latter might occur if the well-described endotoxin-induced vascular hyperpermeability is taken into consideration (9). Nevertheless, intact bacterial lipopolysaccharides are Յ20-kDa macromolecules, and vascular leakage is size-selective (7).…”
Section: G859mentioning
confidence: 99%